Global Trends of Service Quality in Healthcare: A bibliometric analysis of Scopus Database. - Ali, Javed; Jusoh, Ahmad; Abbas, Alhamzah Fadhil; Nor, Khalil Md (The journal of contemporary issues in business and government, 2021)
Purpose: The rising importance of healthcare service quality in the literature led us to conduct a bibliometric analysis of the said area of interest. It aims to investigate the trends and patterns happened in the literature of service quality in healthcare service. Data Source: Scopus database was used to conduct the 4689 papers for bibliometric analysis. Method: VOSviewer software was used to evaluate the research papers associated with healthcare service quality. The Publication trend was analyzed from the year 1969 to 2019 by using Scopus database. The number of documented retrieved and put into the analysis was 4689. The most productive and influential authors were identified. Co-authorship and Co-occurrence analysis were conducted. Findings: Results of Co-authorship and Co-occurrence analysis revealed that the United States and the United Kingdom were leading the publication of documents related to healthcare service quality. Also, the keywords -service quality, satisfaction, healthcare, perception, expectation, performance and SERVQUAL were found to be most prominent in the literature. Conclusion: The bibilometric analysis was conducted to identify the trends in the area of service quality of healthcare sector. The current study identified the publication trend which was potentially increasing and would be increasing in the future. M.Bahadori and Ramin Ravangard were the most influential authors found. Also, co-authorship and cooccurrence analysis was performed to evaluate the countries which are performing at the front and keywords used in the literature.